Self-access language learning: students’ perceptions of and experiences within this new mode of learning (2012)
With the aim of fostering autonomy in learning, both innovations, the self-access centre and the mode of learning derived from it, were adopted in the context of the study (Language Centre in the University of Veracruz, Mexico). Based on a case study, I have adopted a qualitative perspective to do this research, which aimed to know how the students undergoing this new English learning mode perceived it and what their experiences were within the no-class courses. The purpose of this article is to present the main themes that emerged after gathering the data for this study. It concludes with suggestions for a more contextualized and critical adoption of innovations in the English as a Foreign Language arena. En el contexto de este estudio (Centro de Idiomas de la Universidad Veracruzana, México), y con la finalidad de promover la autonomía en el aprendizaje, se adoptaron dos innovaciones: los centros de autoacceso y el aprendizaje de lenguas en ellos. Basándome en una investigación realizada con el fin de conocer cómo perciben y experimentan los estudiantes esta nueva modalidad de aprendizaje de inglés, el propósito del presente artículo es mostrar los principales temas que surgieron a partir de la colecta de datos. El estudio concluye con la sugerencia de que la adopción de innovaciones en el terreno de la enseñanza de inglés como lengua extranjera se haga de manera más contextualizada y sea más crítica.